OP0002 Aortic Dissection Complicating GIANT Cell Arteritis. (10th June 2014) - Makol, A.; Kebed, D.T.; Bois, J.P.; Connolly, H.M.; Foley, T.A.; Askew, J.W.; Maleszewski, J.J.; Greason, K.L.; Schaff, H.V.; Warrington, K.J.; Anavekar, N.S.
Abstract : Background: Aortic aneurysm/dissection is a known complication of giant cell arteritis (GCA), particularly late in the disease course. Rate of growth of aortic aneurysm and risk factors for dissection are largely unknown. Also, there are no established guidelines for monitoring and management of aortic aneurysm in patients with GCA Objectives: 1. To determine average growth rate of aortic aneurysms in GCA. 2. To identify aneurysm size associated with aortic dissection. 3. To describe clinical features and outcomes of aortic dissection. Methods: A retrospective medical record review was performed to identify all patients with GCA and aortic aneurysm diagnosed at our institution between Jan 2000 and Dec 2012. Size of the aneurysm at diagnosis and average growth over time was ascertained. Clinical features and co-morbidities of patients with aortic dissection were abstracted from the medical records. Results: We identified 195 patients (62% female, 94% Caucasian) with GCA and aortic aneurysms. Mean age was 74 years. Of these, 161 (82%) involved the ascending thoracic aorta, 21 (11%) involved the descending thoracic aorta, and 13 (7%) involved the abdominal aorta. Mean aortic size at diagnosis was 49.3 mm (50.1 mm ascending, 51.3 mm descending, 35.7 mm abdominal). Growth rates at 1, 2 and 3 years were 2.04, 3.14 and 4.78 mm from baseline, respectively with an average growth rate of 1.59 mm/year, for first 3 years after diagnosis. There were 14 (7%) aortic dissections and 1 (1%) rupture, all involving the thoracic aorta. Stanford Type A and Type B dissections were seen in 7 (50%) and 7 (50%) cases, respectively. The most common presenting symptoms were chest pain (75%) and syncope (18%). Diagnosis was made by computed tomography, transesophageal echocardiogram, and magnetic resonance angiogram in 80%, 13%, and 7% of cases, respectively. The mean maximal aneurysmal dilation at the time of dissection or rupture was 54±11 mm (range 41–80 mm) at the location of dissection or rupture. Demographics of GCA patients with dissections were similar to those without dissection with mean age of 75 years, 60% were female and all Caucasian. Comorbidities included hypertension (87%), hyperlipidemia (53%), coronary artery disease (60%), and diabetes mellitus (13%). At the time of dissection, 58% were on systemic corticosteroids and 83% were on a beta-blocker. Emergent surgical repair was required in 57% of cases (88% involving the ascending aorta). Overall mortality at 30 days was 14%. Conclusions: In this large series of consecutive patients with GCA and aortic aneurysms, we noted an 8% incidence of acute aortic complications. Aortic dissections develop with a higher frequency in thoracic compared to abdominal aortic aneurysms. These are associated with high mortality and the mean maximal aneurysmal dilation at time of dissection or rupture appears to be lower than that reported for non-inflammatory aneurysms in the literature [1]. Current guidelines for monitoring and management of aortic aneurysms may not apply to the GCA population. References: Elefteriades JA. Ann Thorac Surg. 2002 Nov;74(5):S1877-80; discussion S1892-8. Natural history of thoracic aortic aneurysms: indications for surgery, and surgical versus nonsurgical risks. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2072